Trend of soil salinization in Africa and implications for agro-chemical use in semi-arid croplands - Omotu, G.T.; Kome, G.K.; Ramakhanna, S.J.; Muriza, N.M.; Ruley, J.A.; Jayeoba, O.J.; Raharimanana, V.; Owusu Ansah, A.; Khamis, N.A.; Mathafeng, K.K.; Elmobarak, A.A.; Vargas, R.R.; et al. (Elsevier, 2024)
Soil salinization is a gradual degradation process that begins as a minor problem and grows to become a significant economic loss if no control action is taken. It progressively alters the soil environment which eventually negatively affects plants and organism that were not originally adapted for saline conditions. Soil salinization arises from diverse sources such as side-effects of long-term use of agro-chemicals, saline parent rocks, periodic inundation of soil with saline water, etc. In Africa, soil salinization has not been adequately documented particularly in the croplands. The objective of this study was to identify trends of cropland salinization in Africa and how its relationship with long-term land use practices affected the soil environment. The study analysed soil salinization between 1965 and 2020 using measured electrical conductivity (EC), spatial modelling with environmental covariates, and national statistics on cropland expansion and application of mineral fertilizers, herbicides, and pesticides. The results showed increasing trends of EC in Africa due to climatic and land use drivers. Increasing trends of EC, which evidenced salinization, was found in 31 million hectares of topsoils and 18 million hectares of subsoils. About 2 million hectares of croplands were depicted with salinization and >25 million hectares at the risk of salinization in the arid and semi-arid areas. The study also found statistical relationships between semi-arid cropland salinization and trends of agro-chemical use and cropland sizes. There were significant (p < 0.001) positive correlations between semi-arid cropland salinization and trends of cropland expansion and applied nitrogenous fertilizers. It found that increasing trend of applied mineral nitrogenous fertilizers could double the odds of salinization in semi-arid croplands while cropland expansion could increase the odds of semi-arid cropland salinization by >10 %. These findings present ground-breaking baseline information for future works on sustainable land-use practices that can control cropland soil salinization in Africa.